The Royal Naval Hydrographic Service 1795-1995 - Morris, R. O. (The International Hydrographic Review, 2015)
Two hundred years ago, on 12 August 1795, King GEORGE III signed the Order in Council setting up the Royal Navy's Hydrographic Office. This paper traces its growth from a handful of civilians sorting through a collection of surveys in the Admiralty attics to the surveying and charting organisation of today. It shows how chart folios, sailing directions and notices to mariners were introduced, how a corps of dedicated seaman surveyors was established, and how they and the cartographers have served Britain and the world through 200 years of peace and war.